Home-care educational interventions to prevent complications in patients with Ventricular Assist Devices: a systematic review - Franceschini, G.; Talevi, G.; Maso, S.; Comparcini, D.; Porfiri, M.; Cicolini, G.; Simonetti, V. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The implantation of ventricular assist devices is the only effective alternative to cardiac transplantation in patients with chronic heart failure, in terms of survival and quality of life. However, their implantation can lead to physical and psychological complications, potentially preventable, especially in the long term, through patients’ education. This research aimed to summarize the current best evidence on educational strategies towards patients after implantation of ventricular assist devices, in home-care setting, to reduce the major related complications, namely driveline infections, gastrointestinal bleeding and psychological complications. Study Design. Systematic review. Methods. Title and abstract selection, full-text screening, study quality assessment, and data extraction followed the PRISMA protocol and the Cochrane Handbook for Systematic Reviews of Interventions. The search was conducted through consultation of databases such as Medline, Scopus, EMBASE, and Web of Science, during the period from March 2022 to December 2022, in relation to English-language articles, from search strings processing and inclusion and exclusion criteria.Results. Of the 1,231 items identified, 9 were selected because consistent with the inclusion criteria. The most effective educational interventions toward patients with ventricular assist devices were identified, delivered by multidisciplinary teams coordinated by a professional expert in management of ventricular assist devices, and regularly conducted. In particular, gastrointestinal bleeding and driveline infections could be prevented and reduced by complex, multimodal educational interventions, including telephone and app interventions. Educational strategies based on verbal instructions, hands-on demonstrations, innovative technologies, and active involvement of families/caregivers were particularly effective in preventing psychological complications.Conclusions. Investing time and resources in educating patients with ventricular assist devices is mandatory, given the significant impact of educational outcomes on complications’ reduction. Moreover, educational interventions geared towards patient’s psychological well-being, brings positive outcomes on patient’s compliance too, resulting in promising clinical outcomes. However, more in-depth research is needed, to support professionals in developing effective educational plans for such fragile and complex patients.